The Relationship Between Sleep Quality and Mean Arterial Pressure (Map) Value In The Elderly With Hypertension In The Working Area Of The Palasari Health Center, Subang Regency - Yudi Gumilang Sakti; Novian Mahayu Adiutama; Bayu Nirwana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Abraham Maslow (1984) proposed a hierarchy of needs that includes 5 basic needs and desires in humans. The 5 levels of basic human needs are physiological needs Basic human needs are the elements needed to maintain balance, both physiologically and psychologically. One of them is sleep where humans need to meet their basic needs to achieve optimal energy needs. The current investigation employs a cross-sectional research design, utilizing a correlational approach to examine the research question at hand. The sampling method in this research used simple random sampling, the total sample was 94 respondents. The research instrument used the PSQI questionnaire and digital sphygmomanometer instrument. Where the Spearman Rank test results were obtained with a p-value < 0,001 and a Correlation Coefficient value of 0.503. So, based on the results of this research, it can be concluded that there is a relationship between sleep quality and MAP value in elderly people with hypertension in the work area of ​​the Palasari Health Center, Subang Regency in 2024 with a p-value<0,001 with a positive correlation coefficient. It is expected that the research will serve as a benchmark for future researchers in the field of education, particularly in their endeavors to enhance the quality of sleep in elderly individuals afflicted with hypertension, utilizing the MAP standards.